Specific Features of the Hypothalamic Leptin Signaling Response to Cold Exposure Are Reflected in Peripheral Blood Mononuclear Cells in Rats and Ferrets - Reynés, Bàrbara; Klein Hazebroek, Marlou; García-Ruiz, Estefanía; Keijer, Jaap; Oliver, Paula; Palou, Andreu (Frontiers in Physiology, 2017)
Objectives: Cold exposure induces hyperphagia to counteract fat loss related to lipid mobilization and thermogenic activation. The aim of this study was investigate on the molecular mechanisms involved in cold-induced compensatory hyperphagia. Methods: We analyzed the effect of cold exposure on gene expression of orexigenic and anorexigenic peptides, and of leptin signaling-related genes in the hypothalamus of rats at different ages (1, 2, 4 and 6 months), as well as in ferrets. We also evaluated the potential of peripheral blood mononuclear cells to reflect hypothalamic molecular responses. Results: As expected, cold exposure induced hypoleptinemia in rats, which could be responsible for the increased ratio of orexigenic/anorexigenic peptides gene expression in the hypothalamus, mainly due to decreased anorexigenic gene expression, especially in young animals. In ferrets, which resemble humans more closely, cold exposure induced greater changes in hypothalamic mRNA levels of orexigenic genes. Despite the key role of leptin in food intake control, the effect of cold exposure on the expression of key hypothalamic leptin signaling cascade genes is not clear. In our study, cold exposure seemed to affect leptin signaling in 4-month-old rats (increased Socs3 and Lepr expression), likely associated with the smaller-increase in food intake and decreased body weight observed at this particular age. Similarly, cold exposed ferrets showed greater hypothalamic Socs3 and Stat3 gene expression. Interestingly, peripheral blood mononuclear cells (PBMC) mimicked the hypothalamic increase in Lepr and Socs3 observed in 4-month-old rats, and the increased Socs3 mRNA expression observed in ferrets in response to cold exposure. Conclusions: The most outstanding result of our study is that PBMC reflected the specific modulation of leptin signaling observed in both animal models, rats and ferrets, which points forwards PBMC as easily obtainable biological material to be considered as a potential surrogate tissue to perform further studies on the regulation of hypothalamic leptin signaling in response to cold exposure.